From thrombosis to fibrosis in chronic thromboembolic pulmonary hypertension - Bochenek, Magdalena L.; Rosinus, Nico S.; Lankeit, Mareike; Hobohm, Lukas; Bremmer, Felix; Schütz, Eva; Klok, Frederikus A.; Horke, Sven; Wiedenroth, Christoph B.; Münzel, Thomas; Lang, Irene M.; Mayer, Eckhard; Konstantinides, Stavros; Schäfer, Katrin (Thrombosis and Haemostasis, 2017)
The pathomechanisms underlying the development of thrombofibrotic pulmonary artery occlusions in Chronic Thromboembolic Pulmonary Hypertension (CTEPH) are largely unknown. The aim of this study was to allocate distinct cellular processes playing a role in thrombus resolution, such as inflammation, hypoxia, proliferation, apoptosis and angiogenesis, to different stages of thrombofibrotic remodelling. A total of 182 pulmonary endarterectomy (PEA) specimens were collected from 31 CTEPH patients. To facilitate co-localisation, Tissue MicroArrays were prepared and processed for (immuno)-histochemistry and confocal fluorescence microscopy. Murine venous thrombus formation and resolution was examined after inferior vena cava ligation. PEA tissues exhibited five morphologically distinct regions predominantly consisting of either fibrin-, erythrocyte- or extracellular matrix-rich thrombus, myofibroblasts, vessels or fibrotic tissue, and were found to resemble chronological stages of thrombus resolution in mice. Cellularity was highest in vessel-rich regions, and numerous cells were strongly positive for HIF1α or HIF2α as well as markers of activated VEGF signalling, including endothelial nitric oxide synthase. On the other hand, negative regulators of angiogenic growth factor signalling and reactive oxygen species were also highly expressed. Immune cells, primarily macrophages of the M2 subtype and CD117 haematopoietic progenitors were detected and highest in vascularised regions. Our findings demonstrate the simultaneous presence of different stages of thrombus organisation and suggest that hypoxia-induced endothelial, mesenchymal and immune cell activation may contribute to thrombofibrosis in CTEPH. This systematic histological characterisation of the material obstructing pulmonary vessels in CTEPH may provide a valuable basis for further studies aimed at determining causal factors underlying this disease.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Chronic thromboembolic pulmonary hypertension; fibrosis; histological classification; venous thrombosis